2018
DOI: 10.1108/qrom-10-2016-1440
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and redress procedures: experiences of teachers in Ireland

Abstract: Purpose The purpose of this paper is to report the experiences of redress seeking and organisational responses for targets of bullying. Design/methodology/approach A phenomenological research design was adopted. In total, 22 primary teachers (seven males, 15 females) in Ireland were self-selected for interview, following an advertisement detailing the study in a national teacher union magazine. Data were analysed utilising an interpretative phenomenological analysis framework. Findings All those interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The failure of HR to resolve or even address bullying issues is part of this complex web of power relations and are consistent with the examination of bullying redress seeking experiences of Irish teachers, which identified that the procedures of redress themselves had become technologies of further power and subjugation (Mannix McNamara et al, 2017). All three Universities had, at the time of data collection, anti-bullying policies in place that contained a clearly articulated commitment to a work environment in which staff would be free from bullying in any form, and with detailed procedures for raising contravening issues and behaviors.…”
Section: Discussionsupporting
confidence: 59%
“…The failure of HR to resolve or even address bullying issues is part of this complex web of power relations and are consistent with the examination of bullying redress seeking experiences of Irish teachers, which identified that the procedures of redress themselves had become technologies of further power and subjugation (Mannix McNamara et al, 2017). All three Universities had, at the time of data collection, anti-bullying policies in place that contained a clearly articulated commitment to a work environment in which staff would be free from bullying in any form, and with detailed procedures for raising contravening issues and behaviors.…”
Section: Discussionsupporting
confidence: 59%
“…Further, the formation of safe and independent outlets for reporting toxic behaviours, as suggested by Pelletier [19], should be considered by governing bodies. The results from a study that explored the experiences of Irish teachers when seeking redress for bullying and incivility [53] provided salutary insight into failures to effectively address complaints of workplace incivility and bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that creating safe outlets for followers to report toxic behaviours such as an ethics ombudsman could support the investigation of toxic leadership [19]. Given the poor outcomes for redress seeking among teachers who experience bullying and incivility [53] in the teaching profession (the population of focus in this study), the suggestion of an independent assessor/mediator has some merit. Furthermore, conditions should also be identified under which followers feel safe to challenge a toxic leader.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriation, use, and misuse of power feature widely in the extant literature on workplace bullying [7,10,13,14]. A critical theoretic perspective would position power at the centre, given that according for Foucault, for example, power is "everywhere, not because it embraces everything but because it comes from everywhere, one is never outside it" [15] (p. 141).…”
Section: Workplace Bullying As Misuse Of Powermentioning
confidence: 99%
“…There is consensus in the literature that bullying can have a devastating effect on the physical and psychological wellbeing of the target, yet despite this recognition there remains in many countries (Ireland included), no dedicated legislation addressing the issue of workplace bullying and, as a result, reliance is generally placed on 'Codes of Practice' [5]. In addition, these codes of practice have been described as ineffective in protecting people from bullying at work [6].Certainly teachers' attempts to seek redress for workplace bullying have proven to lack efficacy [7]. Research into the causes of this is still in relative infancy however, initial insights suggest that power and organisational culture are key components for organisational inaction in terms of addressing workplace bullying [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%